2nd coordination sphere controlled electron transfer of iron hangman complexes on electrodes probed by surface enhanced vibrational spectroscopy - Ly, H. K.; Wrzolek, P.; Heidary, N.; Goetz, R.; Horch, Marius; Kozuch, Jacek; Schwalbe, M.; Weidinger, Inez M. (Chemical Science, 2015)
Iron hangman complexes exhibit improved catalytic properties regarding O2 and H2O2 reduction, which are attributed to the presence of a proton donating group in defined vicinity of the catalytic metal centre. Surface enhanced resonance Raman (SERR) and IR (SEIRA) spectro-electrochemistry has been applied concomitantly for the first time to analyse such iron hangman porphyrin complexes attached to electrodes in aqueous solution. While the SERR spectra yield information about the redox state of the central iron, the SEIRA spectra show protonation and deprotonation events of the 2nd coordination sphere. To investigate the influence of a proton active hanging group on the heterogeneous electron transfer between the iron porphyrin and the electrode, two hangman complexes with either an acid or ester functional group were compared. Using time resolved SERR spectroscopy the electron transfer rates of both complexes were determined. Complexes with an acid group showed a slow electron transfer rate at neutral pH that increased significantly at pH 4, while complexes with an ester group exhibited a much faster, but pH independent rate. SEIRA measurements were able to determine directly for the first time a pKa value of 3.4 of a carboxylic hanging group in the immobilized state that shifted to 5.2 in D2O buffer solution. The kinetic data showed an increase of the heterogeneous electron transfer rate with the protonation degree of the acid groups. From these results, we propose a PCET which is strongly modulated by the protonation state of the acid hanging group via hydrogen bond interactions.
CRIS-Team Scopus Importer:2023-03-20